Assessing the influence of perfusion on cardiac microtissue maturation: A heart‐on‐chip platform embedding peristaltic pump capabilities. Issue 8 (1st June 2021) - Cruz‐Moreira, Daniela; Visone, Roberta; Vasques‐Nóvoa, Francisco; S. Barros, António; Leite‐Moreira, Adelino; Redaelli, Alberto; Moretti, Matteo; Rasponi, Marco
Abstract: Heart‐on‐chip is an unprecedented technology for recapitulating key biochemical and biophysical cues in cardiac pathophysiology. Several designs have been proposed to improve its ability to mimic the native tissue and establish it as a reliable research platform. However, despite mimicking one of most vascularized organs, reliable strategies to deliver oxygen and substrates to densely packed constructs of metabolically demanding cells remain unsettled. Herein, we describe a new heart‐on‐chip platform with precise fluid control, integrating an on‐chip peristaltic pump, allowing automated and fine control over flow on channels flanking a 3D cardiac culture. The application of distinct flow rates impacted on temporal dynamics of microtissue structural and transcriptional maturation, improving functional performance. Moreover, a widespread transcriptional response was observed, suggesting flow‐mediated activation of critical pathways of cardiomyocyte structural and functional maturation and inhibition of cardiomyocyte hypoxic injury. In conclusion, the present design represents an important advance in bringing engineered cardiac microtissues closer to the native heart, overcoming traditional bulky off‐chip fluid handling systems, improving microtissue performance, and matching oxygen and energy substrate requirements of metabolically active constructs, avoiding cellular hypoxia. Distinct flow patterns differently impact on microtissue performance and gene expression program. Abstract : A heart‐on‐chip platform integrating an automated peristaltic pumping system is developed as an accurate tool to study the influence of perfusion on cardiac tissue maturation. The study focus on the impact of flow rate on the temporal dynamics of cell morphology, cellular organization, contractile behavior, together with a comprehensive analysis of relevant transcriptional profile.